PENGUJIAN METODE HIDROGRAF SATUAN SINTETIK GAMA I DALAM ANALISIS DEBIT BANJIR RANCANGAN DAS BANGGA - Andiese, Vera Wim (MEKTEK, 2012)
One of the methods to determine design of flood discharge that had been developed in Java are Gama I Synthetic Unit Hydrograph. This method flood hydrograph at rivers with none or very little flood hydrograph observation by using caracteristic or catchment area parameter. But, the physical caracteristic in Java is different if compared in Central Sulawesi, especially Bangga catchment area.The method in this study is to determine the deviation of flood discharge design by Gama I Synthetic Unit Hydrograph method compare with hydrology distribution method (frequency distribution). The analysis method used by Log Person Type III distribution. The result of deviation of value flood discharge design is 2052,9328 % for 2nd return period, 1633,7338 % for 5th return period, 1578,8311 % for 10th return period,1380,4368 % for 25th return period, 1251,4076 % for 50th return period, and 1136,2231 % for 100th return period.